Implementation Of PSAK 109 At Baznas Bangkalan From The Perspective Of Maqashid Syariah - Fathur Rozi; Luluk Hanifah; Mashudi Mashudi (CV. Global Cendekia Inti, 2026)
This research aims to analyze the implementation of PSAK 109 at the National Amil Zakat Agency of Bangkalan Regency from the perspective of maqashid sharia. The issue raised is the suboptimal integration between the technical fulfillment of zakat financial reporting and the reflection of shariah welfare values in practice at the regional level. This research uses a descriptive-analytical qualitative approach thru in-depth interviews, observation of financial report documents, and documentation studies. Analysis was conducted on five components of the financial statements according to standards, namely the statement of financial position, statement of fund changes, statement of management asset changes, cash flow statement, and notes to the financial statements. The research results show that the financial statements have been prepared in accordance with PSAK 109 regulations, with a clear summary distinguishing between zakat funds, infak/sadaqah, amil funds, and non-halal funds. This practice not only meets the aspects of accountability and transparency but also reflects the safeguarding of wealth, life, and trust as per the objectives of maqashid sharia. The management of productive assets and detailed explanations in the notes to the financial statements demonstrate a sustainable orientation toward the welfare of the mustahik.